Evaluation of storage containers and botanical oils for bruchid management in groundnut: Evaluation of storage containers and botanical oils for bruchid management in groundnut - NATARAJA MAHESHALA; POONAM JASROTIA; G HARISH; S D SAVALIA; RAM DUTTA (Journal of Oilseeds Research, 2020)
Storage containers and botanical oils were evaluated for managing bruchids in groundnut. After six monthsstorage, damage to pods in airtight plastic container, APC was less (34.0 and 35.0%, respectively for neem and castor oils) than air-permeable galvanized iron tin, APGIT (75.8 and 73.8%, respectively). Similarly, weight loss of pods stored in APC was less (33.5 and 31.4%, respectively for neem and castor oils) than APGIT (77.8 and 76.1%,respectively). When tested alone, APC was superior to APGIT while, neem and castor oils were statistically nonsignificant. It was noted that treatments and length of storage had no impact on germination.